Comparative analysis of six search engines using terms taken from macrothesaurus for information processing in the field of economics and social development - Mayor, Jansen M.; Cruz, Ma. Divina P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
The growing popularity of Internet as a source of information has fueled the growth of search engines. Search engines are facilities that help users find information through the vast reservoir of knowledge that can be found on the Internet. This study is an evaluation of the performance of the six popular search engines.
The six search engines, Infoseek, Hotbot, AltaVista, Excite, WebCrawler and Lycos were evaluated using terms taken from the 4th edition of Macrothesaurus for Information Processing in the Field of Economics and Social Development. A total of sixty eight terms were randomly taken and were formulated as queries that were then used on the six search engines. Fourteen of the sixty-eight were resubmitted using the search syntax of each search engine. The first ten hits generated were evaluated for their accuracy, reliability and currency. Also evaluated were the ease of use and other features and services provided by the search engines, as well as their support for advance
A total of 4809 hits were evaluated. The result of the test shows that when seeking information on the social sciences, Infoseek garnered the top rank, followed by Excite, AltaVista, Hotbot, WebCrawler and Lycos. The low score that each search engine got can be attributed to two factors, spamming and the ambiguities caused by the complexity of language used in indexing and in searching.
This paper also tackles the factors that affect the indexing and ranking of sites. the factors that affect the quality of the index of a search engine are size, the number of pages that the spiders can crawl in a day, freshness of the index, the number of days before a submitted or a non-submitted page get indexed, depth, frames support, password protected sites, link popularity, learns frequency, robot.txt and meta robots. The factors that affect how search engine rank sites are the extra boost given to reviewed sites, link popularity, meta tags, the presence of invisible texts and tiny texts, indexing of the comment and ALT attribute of an image, the use of stop words, stemming and case sensitivity.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Web search engines; World Wide Web (Information retrieval system).; Online bibliographic searching